EDUKASI PEMANFATAN GOOGLE CLASSROOM DALAM PEMBELAJARAN ONLINE SISWA SD N 2 BLAHKIUH - Ida Ayu Made Wedasuwari; Ni Wayan Eminda Sari (Bajang Institute, 2023)
The purpose of this community service is to provide assistance and understanding to students about using Google Classroom as a learning medium during the Covid 19 pandemic to help teacher and student interaction. The methods used in this service are preparation, implementation, mentoring, and evaluation. The results of the analysis show that the effectiveness of the google classroom utilization training is 93.87%, which means that this activity is considered very good for helping students learn online. The success of this service is supported by the active participation of students and teachers of SD N 2 Blahkiuh.